Humor by Numbers: An Analysis of Comedians' Mathematical Thinking Patterns in Creating Stand-Up Material with Induction, Deduction, and Analogy - Aji, Fauzan Bayu; Sugianto, Rahmad; Usmiyatun, Usmiyatun (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
Thinking is an activity that takes place in the mind/brain of each individual in order to synthesize problems to solve them, understand concepts, remember, create methods, or analyze events. Students will be able to analyze when they are able to use their thinking skills to understand a concept. By presenting learning that is designed with a comedy structure in the classroom, it can make the class atmosphere more enjoyable by not letting go of the concept or material being taught in order to achieve learning objectives, namely by Stand Up Comedy. This study aims to describe how comedians' mathematical thinking processes in high school students in Mathematical Logic material based on their mathematical abilities. This type of research is exploratory qualitative by collecting verbal data. Data analysis techniques use inductive, deductive, and analogy methods. The subjects used were 3 class XI students who had different mathematical abilities. The result of this study is that comedians think mathematically by using inductive, deductive, and analogy methods when writing Stand Up Comedy materials. Students' understanding of concepts is obtained from the thinking processes carried out by students, starting from the setup development process to the assimilation and accommodation processes. While the fun atmosphere in learning is obtained from the findings of the concepts they learn where in drawing conclusions using inductive, deductive, and analogy methods can trigger laughter from the audience.